2019
DOI: 10.1302/1863-2548.13.190076
|View full text |Cite
|
Sign up to set email alerts
|

Additional challenges in children with idiopathic clubfoot: Is it just the foot?

Abstract: Purpose Treatment of idiopathic clubfoot (IC) has improved since the introduction of the Ponseti method. However, relapses are still common and primarily related to non-adherence to the brace regime. Our hypothesis was that IC might be more than just a structural deformity. Based on three studies, the aim of this paper was to provide an overview of findings regarding additional challenges within IC. Methods In total, 153 children with IC and 137 control children participated in the studies. The first study ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Some defects, such as clubfoot and polydactyly, can be corrected through surgery. Even so, body function and health‐related quality of life are still affected in most offspring after treatment 6,7 . The aetiology of limb defects is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Some defects, such as clubfoot and polydactyly, can be corrected through surgery. Even so, body function and health‐related quality of life are still affected in most offspring after treatment 6,7 . The aetiology of limb defects is complicated.…”
Section: Introductionmentioning
confidence: 99%
“… 47 Recent studies have shown that there is a slightly higher prevalence of neurodevelopmental difficulties in children with isolated clubfoot which is also consistent with this observation. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the validity of the measure in truly documenting functional deficits in the patient with a unilateral clubfoot or a less severe bilateral foot, may be suspect. Other researchers have also evaluated motor function ability in children initially treated with Ponseti casting (62,63). While Aulie et al reported 76% of patients with clubfoot treated either surgically or with Ponseti casting, were classified with normal motor abilities (62), Lӧӧf suggests global deficits that may affect a child's perception of their quality of life (63).…”
Section: Historymentioning
confidence: 99%
“…Other researchers have also evaluated motor function ability in children initially treated with Ponseti casting (62,63). While Aulie et al reported 76% of patients with clubfoot treated either surgically or with Ponseti casting, were classified with normal motor abilities (62), Lӧӧf suggests global deficits that may affect a child's perception of their quality of life (63). It is imperative to understand the objective of the assessment (global motor function or joint specific), when interpreting the results.…”
Section: Historymentioning
confidence: 99%